ECONOMIC ANALYSIS OF ARTISANAL FISHERIES VALUE CHAIN IN EPE LAGOON, LAGOS STATE, NIGERIA - ABASILIM , C. F.; SAMUEL , O. B.; ONYEWUCHI , I. V. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study analysed the artisanal fisheries value chain in Epe lagoon, Lagos State, Nigeria. The study profiled the socioeconomic characteristics, analyzed the profitability and constraints of the value chain actors. A stratified sampling technique was adopted in selecting 120 respondents for three value chain strata: fisher folks, fish marketers and fish processors. Each value chain comprised of 40 respondents. Data analysis revealed gender bias in the value chain activities as only males were fisher folks, only females were fish processors while most females were fish marketers. Only 5% of the young adults were involved in the value chains. The BCRs were 1.13, 1.70 and 1.60 respectively for fisher folks, fish marketers and fish processors. The net margin analysis showed that the average fisher folk, relative to other actors lived, on lowest daily margin. This can be attributed to the high start-up capital compared with the other two value chains. The most severe constraints faced were lack of credit for expansion and inadequate storage facilities. The purchase prices offered for their products and their non-membership in cooperative societies were considered as the least severe constraints faced by the value chain actors. It is recommended that improved access to rural credit, storage facilities and infrastructure and subsidized costs of fishing equipment should be a priority while value chain actors should be educated on the need and how to organise themselves into cooperative societies. Youths should be encouraged to explore the potentials in the artisanal fisheries value chain in order to reduce the level of unemployment.